Poly-Victimization Among Female College Students: Are the Risk Factors the Same as Those Who Experience One Type of Victimization? - Snyder, Jamie A.; Scherer, Heidi L.; Fisher, Bonnie S. (Violence against women, 2021)
Past research has shown that a significant proportion of college students will experience a victimization during their college tenure. This body of research provides evidence that college students’ lifestyle characteristics and routine activities play a role in influencing their risk of victimization; yet, little is known about whether these same risk factors predict both single-type victimization and poly-victimization. Using a sample of more than 4,000 college women from across the United States, multivariate analyses were used to examine the risk factors for poly-victimization. Measures from both target congruence theory and lifestyles-routine activities theory were found to significantly differentiate single-type victims from poly-victims.